GAMBARAN KEADAAN SANITASI RUMAH DI KELURAHAN KEROBOKAN KAJA KABUPATEN BADUNG TAHUN 2023 - Lestari, Ni Nyoman Anom Ary; Aryana, I Ketut; Purna, I Nyoman; Indayani, Iin (Poltekkes Kemenkes Denpasar, 2024)
Abstract. Kerobokan Kaja is a village in North Kuta District, Badung Regency. A house is a physical structure or building that is used as a shelter where the environment is beneficial to physical and spiritual health as well as social conditions that are beneficial to the health of individuals and families. The number of heads of families in the Kerobokan Kaja Village is 3,876 households. This study aims to determine the state of house sanitation in the Kerobokan Kaja Village in 2023 based on the Ministry of Health 2002, In the questionnaire there are 3 aspects that are assessed, namely the components of the house, sanitation facilities and the behavior of residents by conducting interviews and observations of the head of the family and other family members. This study uses a descriptive study because researchers want to see the existing conditions. Based on the results of surveys and observations conducted by taking a sample of 68 families. The results obtained were 35 houses (51%) that did not meet the requirements, while 33 houses (49%) did. Efforts for residents in the Kerobokan Kaja Village are expected to pay more attention to the cleanliness and sanitation of their homes. Keywords: Home sanitation, home components